VKORC1 single nucleotide polymorphisms in rodents in Spain. (December 2022) - Bermejo-Nogales, Azucena; Rodríguez Martín, José A.; Coll, Julio; Navas, José M.
Abstract: Rodents are considered one of the animal pests with the greatest impact on agricultural production and public health. Anticoagulant rodenticides (ARs), used as one of the most effective ways to control rodent populations worldwide, inhibit the vitamin K 2, 3-epoxide reductase (VKORC1) enzyme involved in blood coagulation. Resistances to ARs are mainly associated with mutations or single nucleotide polymorphisms (SNPs) in the vkorc1 gene. Since the information on this subject is scarce in Spain, we monitored and discovered rodent SNPs that could favour genetic resistance in its populations. For that, more than 200 samples of stools and tails from brown rat ( Rattus norvegicus ), black rat ( Rattus rattus ) and mouse ( Mus musculus ) were collected from 12 Spanish regions previously identified with low AR efficacy in coordination with the National Association of Environmental Sanitation Companies (ANECPLA) and the managing entities of four locations. We then sequenced their vkorc1 exon 3 corresponding genomic DNA. We identified genotypic vkorc1 variations corresponding to amino acid changes at the VKORC1 protein at the S149I – S149T and the E155K - E155Q mutations, depending on the rodent species. Computational analysis of binding predictions found out that the brown rat S149I mutation predicted a high reduction of the binding affinity of chlorophacinone and brodifacoum ARs while, the black rat S149T, E155K and E155Q mutations slightly reduced bromadiolone AR binding. These results suggest that these mutations may be one of the causes of the increased resistance to those ARs. Graphical abstract: Image 1 Highlights: Assessment of AR genetic resistance in Spanish populations of pest rodents. A minimum number of DNA form faecal samples per area must be used. Specie-specific polymorphic nucleotide positions were found. Intensive land use may determine AR resistance. Pest control requires continuous evaluation of genetic resistance.